Necrotizing sarcoid granulomatosis causing compressive myelopathy at cranio-vertebral junction - Anju Shukla; Manu Rastogi; Mazhar Husain; Sunil Dabadghao (Indian Journal of Neurosurgery)
Necrotizing Sarcoid Granulomatosis is the term given to a variant of Sarcoidosis in which the granulomas show necrosis and evidence of angitis. This variant of sarcoidosis tends to involve the lungs primarily; however central nervous system (CNS) involvement has also been reported. We report here a case of extra-dural cord compression at cranio-vertebral junction with no other systemic involvement and excellent clinical response to corticosteroids alone. Recognition of this rare variant of sarcoidosis by the pathologist and prompt institution of corticosteroids by the clinician will generally give very gratifying results, as was seen in the present case.